GROWTH PATTERN, BIOMASS ALLOCATION AND RESPONSE OF CRYPTOCORYNE FERRUGINEA ENGLER (ARACEAE) TO SHADING AND WATER DEPTH - Ipor I B; Tawan C S; Basrol M (Tropical Life Sciences Research, 2006)
The ecological study of Cryptocoryne ferruginea Engler was carried out at three different localities, vis. Sabal Kruin, Balai Ringin and Sungai Kerait. The growth pattern and biomass allocation of C. ferruginea were significantly varied between localities, light intensity and water depth as demonstrated by their total dry weight of both plants and leaves, leaf area and total plants in 1 m × 1 m quadrate. The leaf weight ratio (LWR), root weight ratio (RWR), leaf area ratio (LAR), rhizome weight ratio (UWR), specific leaf area (SLA), dry matter production (DMP), nett assimilation ratio (NAR) and leaf area duration (LAD) were significantly differed between light intensity and water depth. Light condition and water depth were also significantly influenced the rate of photosynthesis and light curve pattern. Twenty-seven trees species (118 individuals) were recorded at Sabal Kruin and 18 trees species from 88 individuals at Balai Ringin from five plots of 20 m × 10 m. The estimation of total above ground biomass was 94.26 ton/ha at Sabal Kruin and 128.64 ton/ha at Balai Ringin with the basal area of 1936.42 m2/ha and 2336.75 m2/ha, respectively. The estimated above ground biomass of the abandoned rubber farm at Sungai Kerait was 172.51 ton/ha. The dominant species at Sabal Kruin forest was Neonauclea synkorynes Merr. (Iv = 32.64), followed by Ptychopyxis arborea (Merr.) Airy Shaw (Iv = 22.42), Ilex cymosa Blume (Iv = 11.15), Glochidion littorale Bl. (Iv = 11.09) and Shorea seminis (de Vriese) Stooten (Iv = 10.31). However, forest at Balai Ringin was dominated by P. arborea (Iv = 45.09), followed by Baccaurea bracteata M.A. (Iv = 41.33), N. synkorynes (Iv = 35.65), Litsea nidularis Gamble (Iv = 29.48) and Aglaia rubiginosa (Hiern) Pannell (Iv = 23.23). Water pH at Balai Ringin and Sungai Kerait were both in acidic condition with pH of 5.24 and 5.11, respectively. The water temperatures were 25.5°C and 25.4°C, while the dissolved oxygen capacity were 1.36 mg/l in Balai Ringin and 2.06 mg/l at Sungai Kerait. The highest CEC (62.23 + cmol/kg) was recorded at Sabal Kruin, followed by Balai Ringin (39.79 + cmol/kg) and Sungai Kerait (19.80 + cmol/kg). Sungai Kerait have the highest percentage of clay (14.51%) compared to Sabal Kruin (9.36%) and Balai Ringin (7.59%). Kajian ekologi Cryptocoryne ferruginea Engler telah dijalankan di tiga kawasan berasingan, iaitu Sabal Kruin, Balai Ringin dan Sungai Kerait. Corak pertumbuhan dan peruntukan biojisim C. ferruginea adalah berbeza dengan signifikan antara kawasan, keamatan cahaya dan kedalaman air seperti yang telah ditunjukkan oleh nilai jumlah berat kering pokok dan daun, luas daun dan jumlah tumbuhan di dalam kuadrat berukuran 1 m × 1 m. Nisbah berat daun (LWR), nisbah berat akar (RWR), nisbah luas daun (LAR), nisbah berat rizom (UWR), luas daun spesifik (SLA), pengeluaran berat bahan (DMP), nisbah asimilasi (NAR) dan jangka luas daun (LAD) adalah berbeza dengan signifikan antara keamatan cahaya dengan kedalaman air. Keadaan cahaya dan kedalaman air juga mempengaruhi dengan signifikan kadar fotosintesis dan corak lengkung cahaya. Dua puluh tujuh spesies pokok berkayu (118 individu) telah direkodkan di Sabal Kruin dan 18 spesies pokok berkayu daripada 88 individu direkodkan di Balai Ringin daripada lima plot berukuran 20 m × 10 m. Anggaran jumlah biojisim permukaan tanah ialah 94.26 tan/ha di Sabal Kruin dan 128.64 tan/ha di Balai Ringin dengan luas pangkal 1936.42 m2/ha dan 2336.75 m2/ha masing-masing. Anggaran jumlah biojisim permukaan tanah bagi ladang getah yang terbiar di Sungai Kerait ialah 172.51 tan/ha. Spesies paling dominan di Sabal Kruin ialah Neonauclea synkorynes Merr. (Iv = 32.64), diikuti oleh Ptychopyxis arborea (Merr.) Airy Shaw (Iv = 22.42), Ilex cymosa Blume (Iv = 11.16), Glochidion littorale Bl. (Iv = 11.09) dan Shorea seminis (de Vriese) Stooten (Iv = 10.32). Manakala hutan di Balai Ringin telah didominasi oleh P. arborea (Iv = 45.09), diikuti oleh Baccaurea bracteata M.A. (Iv = 41.33), N. synkorynes (Iv = 35.65), Litsea nidularis Gamble (Iv = 29.48) dan Aglaia rubiginosa (Hiern) Pannell (Iv = 23.23). pH air di Balai Ringin dan Sungai Kerait adalah berasid dengan pH 5.24 dan 5.11 masing-masing. Suhu air ialah 25.5°C and 25.4°C, manakala keupayaan oksigen terlarut ialah 1.36 mg/l di Balai Ringin dan 2.06 mg/l di Sungai Kerait. CEC tertinggi (62.23 + cmol/kg) direkodkan di Sabal Kruin, diikuti oleh Balai Ringin (39.79 + cmol/kg) dan Sungai Kerait (19.80 + cmol/kg). Tanah di Sungai Kerait mengandungi peratusan tanah liat paling tinggi (14.51%) berbanding di Sabal Kruin (9.36%) dan Balai Ringin (7.59%).